Vehicle Delay-Driven Passenger Delay Modelling: An Agent-Based Copenhagen Case Study - Paulsen, Mads; Rasmussen, Thomas Kjær; Nielsen, Otto Anker (Proceedings from the Annual Transport Conference at Aalborg University, 2018)
Travel time of passengers is often uncertain due to lack of punctuality of public transport services. Whereas Automatic Vehicle Location (AVL) data makes it easy to measure the punctuality of public transport vehicles themselves, calculating door-to-door passenger punctuality is challenging, as both the intended and realised routes of passengers have to be considered. This study introduces a MATSim mesoscopic simulation framework for evaluating passenger punctuality caused by vehicle delays in the railway system in the metropolitan area of Copenhagen. Based upon empirical train delay data for 65 weekdays in the autumn of 2014, the model shows that passenger punctuality is considerably smaller than train punctuality, with 17.8% of the passengers using the railway system being delayed more than a minute compared to their intended plan.